Persepsi Mahasiswa terhadap Peran Guru Laki-Laki dalam Pendidikan Anak Usia Dini - Putri Harianti; Nurhasanah Bakhtiar; Ilham Kurnia (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The presence of male teachers in early childhood education (ECE) remains very limited due to strong gender stereotypes in society. This study aims to explore students’ perceptions of the roles, challenges, and contributions of male teachers in early childhood education. Using a qualitative approach, data were collected through in-depth interviews and focus group discussions (FGDs) involving Master's students in ECE. The findings indicate that male teachers are not merely complementary figures, but essential elements in creating a diverse and inclusive educational environment. They contribute to fostering discipline, responsibility, and serve as positive role models, especially for children who need a male figure. However, their presence often faces challenges such as social stigma and lack of community support. This study highlights the need for policies that support increasing the number of male teachers in ECE to promote a more inclusive and gender-equitable education system.